ANALISIS SPASIAL PERUBAHAN MANGROVE DI WILAYAH PESISIR KABUPATEN GRESIK PROVINSI JAWA TIMUR - Sodikin Sodikin; Rahmat Hidayat; Gusti Nurdin; Moh. Syaiful Anwar (JURNAL PERIKANAN DAN KELAUTAN, 2024)
Mangrove is a coastal ecosystem that plays a very important role in the balance of the coastal environment. The existence of mangroves is very beneficial for the ecology, social and economy of coastal areas. So that the preservation of mangrove areas is very important to do.This study aims to map the changes in mangroves that occur in the coastal area of Gresik Regency, East Java Province.The method in the study uses a spatial approach with remote sensing technology, the distribution and area of mangroves were obtained from Landsat satellite imagery in 2000, 2010 and 2023. Validation was carried out by field ground checks, in addition, analysis to determine the type of vegetation was carried out using the transect line technique. The results of the study showed that in general in the period from 2000 to 2023 mangroves in the coastal area of Gresik Regency increased, in 2000 it had an area of 1529.16 ha, and in 2010 it increased to 1175.77 ha, and in 2023 mangroves in Gresik Regency in general increased again to 2784.45 ha. In the period 2000-2010 mangroves in several sub-districts experienced a decline, but in the period 2010-203 mangroves mostly experienced an increase, except in Kebomas Sub-district which experienced a decline. This happened because of the increasing number of mangrove rehabilitation activities carried out by the government and local communities and the large sedimentation from the Bengawan Solo River. The mangrove decline factor that occurred in the Kebomas Sub-district area occurred because of the large conversion of mangrove land into other uses, such as for housing, fish ponds and industry.